UPAH PANEN PEKERJA TANI SAWAH (Analisis Sosiologi Gender Tentang Perbedaan Upah Antar Pekerja Perempuan dengan Pekerja Laki-laki dari Jenis Pekerjaan yang Sama di Nagari Riak Danau, Kecamatan Basa Ampek Balai Tapan, Kabupaten Pesisir Selatan) - Utari, Riska - (Pendidikan Sosiologi, 2014)
Workers women and men doing the same work the rice fields, the rice harvest, with the same time, in the same location and the same job but getting different pay. Therefore the formulation of the problem, namely